OPTIMALISASI LIMBAH PETERNAKAN DAN BAHAN ALAMI MELALUI SOSIALISASI DAN DEMONSTRASI PUPUK ORGANIK DAN PESTISIDA NABATI - Rima Tri Fatmawati; Angelica Fatimah Fatmawati; Aisyah Latifah; Anisa Zahra Naufani; Diah Ayu Argiyanti Saputri; Shasya Elyandra Salsabila; Fathika Fadhiella Anhar; Zidan Maulana; Hubert Christian Kanilod Sitohang; Irwan Iftadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Sustainable agriculture is an approach aimed at increasing agricultural productivity while maintaining environmental sustainability and improving farmers’ welfare. One of the major challenges in modern agriculture is the excessive reliance on chemical fertilizers and pesticides, which can lead to soil degradation, environmental pollution, and pest resistance. Therefore, the use of organic fertilizers and botanical pesticides has been increasingly promoted as environmentally friendly alternatives. Organic fertilizers, derived from decomposed organic materials such as animal manure and plant residues, play a significant role in improving soil structure, enhancing microbial activity, and increasing the soil’s capacity to retain water and nutrients. Meanwhile, botanical pesticides, obtained from plant-based materials containing bioactive compounds such as alkaloids, flavonoids, saponins, and tannins, function as contact poisons, stomach poisons, repellents, and antifeedants against pests. The integration of organic fertilizers and botanical pesticides supports sustainable agricultural systems by reducing environmental impacts and promoting ecological balance. In addition, the utilization of locally available resources contributes to cost efficiency and enhances farmers’ independence. However, the adoption of these technologies remains relatively low due to limited knowledge and technical skills among farmers. Therefore, educational efforts through socialization and demonstration activities are essential to improve farmers’ understanding and implementation of environmentally friendly agricultural practices. In conclusion, the integration of organic fertilizers and botanical pesticides represents a strategic approach to achieving sustainable agriculture by improving soil fertility, controlling pests effectively, and preserving environmental health.